Development Of Comic Media On Learning Theme 7 Sub-Theme 4 In Third Grade Elementary Schools - Kristiyanto, Daniel; Rahayu, Theresia Sri (International Journal of Elementary Education, 2020)
The lack of concrete learning media affects student learning outcomes, requiring learning media to motivate students to learn. This study aimed to develop comic media in learning Theme 7, Sub-theme 4 to improve third-grade elementary school students' learning outcomes. This research is development research, using the 4D development model. The subject of this research is the validity of comic media. The data collection method used was providing validation sheets to experts. The instrument used was a non-test instrument in the form of a comic media validation sheet. The data analysis technique used is quantitative statistical analysis. This development results indicate that the validation results on the material expert test obtained results with a score of 44 with a percentage of 73%. The media expert test results obtained a score of 90, with a percentage of 90%. So it can be concluded that the development of comic media in learning theme 7 sub-theme 4 to improve student learning outcomes is declared valid. This research implies that comic media can create student interest in learning and reading interest.